Reconfigurable microstrip combline filter with tunable center frequency and bandwidth - Wenxing Tang; Jiasheng Hong (Asia-Pacific Microwave Conference 2011, 2011)
This is paper presents a recent investigation of electronically reconfigurable microstrip combline bandpass filter with both tunable center frequency and bandwidth. Varactors are deployed for continuous tuning. The results of EM simulation and experiment are described.